On the System of Place Name Signs in Estonian Sign Language - Liina Paales (Journal of Ethnology and Folkloristics)
A place name sign is a linguistic-cultural marker that includes both memory and landscape. The author regards toponymic signs in Estonian Sign Language as representations of images held by the Estonian Deaf community: they reflect the geographical place, the period, the relationships of the Deaf community with hearing community, and the common and distinguishing features of the two cultures perceived by community's members.